INNOVATIVE TEACHING TECHNOLOGIES IN "FOREIGN LANGUAGE" CLASSES (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
The article considers the problem of study and implementation of new teaching methods. The article considers the need for modernization of education through key areas connected with improving the effectiveness of training in subject disciplines. The article emphasizes the possibility of using innovative methods of teaching foreign languages, based on an innovative approach, aimed at the development and self-improvement of the individual, at the disclosure of its reserve capabilities and creative potential.